A one-year prospective study of the safety, tolerability and pharmacokinetics of the highest available dose of paliperidone palmitate in patients with schizophrenia - Coppola, Danielle; Liu, Yanning; Gopal, Srihari; Remmerie, Bart; Samtani, Mahesh N.; Hough, David W.; Nuamah, Isaac; Sulaiman, Ahmad Hatim; Pandina, Gahan (BMC, 2012)
Background: There are no previous reports of paliperidone palmitate’s (PP) long term tolerability or pharmacokinetics of the highest dose in patients with schizophrenia. This study evaluates safety and tolerability, as well as pharmacokinetics, of the highest marketed dose of PP (150 mg eq. [234 mg]) in stable patients with schizophrenia over a 1-year period. Methods: In this 1-year prospective study, eligible patients (aged 18-65 years; Positive and Negative Syndrome Scale’s total score ≤ 70) received an initial deltoid injection of PP 150 mg eq. The second injection one week later and subsequent once-monthly injections were deltoid or gluteal. All injections were to be PP 150 mg eq. Patients willing to participate in intensive pharmacokinetic sampling were classified as Treatment A. Patients unwilling to undergo intensive pharmacokinetic sampling or unable to tolerate the 150 mg eq. dose (consequently receiving flexible doses of 50, 100 or 150 mg eq.) were classified as Treatment B. Results: Of the 212 patients (safety analysis set), 73% were men; 45% white; 20% black; 34% Asians; mean (SD) age 41 (10.2) years, and mean (SD) baseline Positive and Negative Syndrome Scale total score 54.9 (9.03). A total of 53% (n = 113) patients completed the study and 104 received PP 150 mg eq. throughout. Mean (SD) mode dose of PP was 144.8 (19.58) mg eq. The dosing initiation regimen resulted in rapidly achieved and maintained therapeutic paliperidone levels over the study (average concentrations during the dosing interval were 34.7, 40.0, and 47.8 ng/ mL after the 2nd, 8th, and 14th injection respectively). Most frequent (≥ 10%) treatment-emergent adverse events were nasopharyngitis (n = 37), insomnia (n = 32), injection-site pain (n = 32), headache (n = 28), and tachycardia (n= 27). Akathisia (n = 19) and tremor (n = 11) were the most common extrapyramidal adverse events. 33 patients had an SAE and 27 discontinued due to treatment-emergent adverse events. No deaths were reported. Mean (SD) weight change from baseline was 2.5 (5.41) kg at endpoint. Patients’ psychoses remained stable. Conclusions: Safety results after one-year therapy with the highest available dose of once-monthly paliperidone palmitate were consistent with results from previous studies, with no new concerns noted. Plasma concentrations were within the expected range.